Extraction of lipids from microalgae using fluidisation - Visawa Janani Vidya Sankar (2013)
Microalgae are promising sources of lipids and are widely being investigated today for their capacity as a starting material for biodiesel production. One of the major constraints in handling algae and extracting lipids in large scale is the dewatering/drying step and the overall cost it incurs. This study proposes fluidisation as a new method for extracting lipids in the presence of water. The algal cells were exposed to different bubbling conditions; assisted with and without solids. The effects of the bubbles on cells and thus lipid extraction from the wet biomass were measured in terms of the amount of fatty acids obtained after trans-esterification determined using gas chromatography. The results were supported by scanning electron microscopic images which showed the morphological changes due to the hydrodynamic stress offered by the bubbles on the cells and on the introduction of solids. The results indicated that bubbling at higher velocities, 25cm/s has a positive effect towards lipid extraction in the presence of water, than operating at lower velocities. With the solids involved, cell disruption was clearly seen at relatively higher velocities; and short time exposure to fluidisation at that velocity was found to be effective in terms of lipid extraction.